2020
DOI: 10.1097/jnc.0000000000000140
|View full text |Cite
|
Sign up to set email alerts
|

Exploring HIV-Related Stigma as a Determinant of Engagement in HIV Care by African American Women

Abstract: Engagement in HIV care reduces HIV-related health disparities that persist across racial/ethnic and gender lines, yet African American (AA) women face multiple challenges to remaining engaged in care, including HIV-related stigma. We analyzed longitudinal data from 239 participants in the Unity Health Study to estimate associations between HIV-related stigma and engagement in care among AA women linked to HIV care. In adjusted Poisson regression analyses, engagement in care was not associated with HIV-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Our study did not find an association between HIV related stigma and retention in HIV care. This is similar to what was found in other studies [ 36 38 ]. However, there are studies which showed that HIV related stigma was associated with retention in HIV care [ 39 45 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study did not find an association between HIV related stigma and retention in HIV care. This is similar to what was found in other studies [ 36 38 ]. However, there are studies which showed that HIV related stigma was associated with retention in HIV care [ 39 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…The difference in our findings could also be due to our strict definition of retention as some studies that found an association between HIV related stigma and retention in care have defined poor retention as going 12 months since the last documented clinic visit [ 43 ]. Some authors have also suggested that HIV related stigma may hinder initial linkage to care but play a lesser role on retention of patients in care [ 36 ]. This may explain the lack of association between HIV related stigma and retention in care for those already linked to care.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma has been widely assessed and examined in studies on various health and psychiatric conditions: human immunodeficiency virus (HIV), hepatitis C virus (HCV), obesity, major depressive disorder, generalized anxiety disorder, bipolar disorder, alcohol and substance use, and type 2 diabetes mellitus (T2DM) [64][65][66][67][68][69][70][71][72][73]. Respective studies have demonstrated that stigma is commonly experienced by people with specific health and psychiatric conditions, and that stigma is negatively associated with multiple outcomes: suboptimal health or help-seeking behaviors, low engagement in health care, low treatmentseeking behaviors, and low testing or diagnostic uptake.…”
Section: Stigmamentioning
confidence: 99%
“…Clinical trial tests of anti-HIV stigma approaches include a faith-based intervention for Black churches [ 77 79 ], a group-level intervention for Black women [ 80 ], and a community-level intervention for young Black men [ 81 , 82 ]. Whereas Rao and colleagues [ 80 ] did not find group differences in stigma reduction, follow-up analyses reveal important impact of HIV stigma on viral load [ 83 ] and engagement in HIV care [ 84 ], and the mediating role of depression and ART non-adherence [ 58 ].…”
Section: Nih Icos With Hiv-related Stigma Research Approaches and Activitiesmentioning
confidence: 99%